Boosting ecosystem services in rural landscapes : perspectives on actions and evidence :Powerpoint - Willemen, L. (University of Twente, 2020)
This lecture presents: ES in Rural landscapes session; Session topics; Morning programme; Afternoon programme; Reporting back.